Publisher Volume 18 Ius Doctrina Magazine - Fajardo Torres, Anahí (2025)
This new edition of our magazine presents a variety of topics of interest that encourage legal discussion, with a focus on labor law, human rights, property law, cybercrime, and philosophical reflections related to the legal field.